A real-time comparison of mercury accumulation on noble metal thin films using gravimetric device. (December 2016) - Kabir, K.M. Mohibul; Kandjani, Ahmad Esmaielzadeh; Harrison, Christopher J.; Ippolito, Samuel J.; Sabri, Ylias M.; Bhargava, Suresh K.
Abstract: We simultaneously compared and analyzed the mercury sorption and sensing performance of gold, silver, palladium and platinum using quartz crystal microbalance (QCM). Overall, the Au- and Ag-QCM showed superior Hg sensing performance over the Pd- and Pt-counterparts when tested toward a range of concentrations (24–365 ppbv ) at various operating temperatures (35–105 °C). However, it was also found that the Hg sensing performance of each metal varied significantly with the operating temperature and is dependent on the concentration tested. For instance, the Ag-QCM exhibited 57% higher response magnitude than the Au-QCM when exposed toward 24 ppbv of Hg 0 vapor at 35 °C; however, the opposite trend was observed when the same concentration of Hg 0 vapor was tested at 105 °C, with Au-QCM showing 104% higher response magnitudes compared to the Ag-QCM. Moreover, the Ag-QCM showed higher response magnitudes than the Au-QCM for exposure toward 365 ppbv of Hg 0 vapor regardless of the operating temperature. Highlights: Mercury sorption and sensing performance of noble metals such as Au, Ag, Pd and Pt was analyzed using QCM. Au- and Ag-QCM exhibited superior Hg sensing performance than the Pd- and Pt-. Response characteristics varied between Au- and Ag-QCM with the tested Hg 0 vapor concentrations and temperatures.